Exploring the Mediating Role of Entrepreneurial Motivation in the Relationship between Cooperative Performance, Product Innovation, and Economic Independence in Indonesian Islamic Boarding Schools - Puji Astutik; Noor Shodik Askandar; Jeni Susyanti (LP2M IAIN Palopo, 2025)
This study aims to analyze the performance of Koppontren and innovation of Islamic boarding school products towards economic independence with entrepreneurial motivation as a mediating variable in Ngalah Pasuruan Islamic boarding school. This study uses a quantitative approach with the technique of partial least squares structural equation modeling (PLS-SEM). Data were collected through questionnaires distributed to 98 students at Ngalah Pasuruan Islamic boarding school. The results of the study indicate that Koppontren performance and innovation of Islamic boarding school products have a positive and significant effect on economic independence. Furthermore, Koppontren Performance and innovation of Islamic boarding school products have a negative and insignificant effect on economic independence through entrepreneurial motivation as a mediating variable. This finding shows that the institutional performance of Koppontren and Islamic boarding school efforts in carrying out product innovation, both through product development, is unable to increase the economic independence of Islamic boarding schools if their influence is channeled through entrepreneurial motivation. This study contributes to empirical evidence in Islamic boarding school management and entrepreneurship, institutional economics, and Islamic boarding school-based social entrepreneurship.